Analysis of Village Asset Management at The Naga Timbul Village Office, Tanjung Morawa District, Deli Serdang Regency - Galih Supraja; Fiqri Haikal; M. G. Fahluzi (Future Science, 2023)
This research aims to find out and describe the role of village asset management carried out by village officials. Apart from that, it also describes the inhibiting factors in managing village assets. This research was carried out at Naga Timbul Village Office, Tanjung Morawa District, Deli Serdang Regency. This type of research is qualitative research with a descriptive approach to describe the role of village asset management in improving the welfare of village people. The data collection techniques used by researchers are mostly interviews and observations. From the research results, it can be concluded that in managing village assets, village officials lack skilled skills in managing village assets so that this is a major inhibiting factor for village government. Apart from that, village officials should be more active in providing outreach and guidance regarding the important role of managing village assets for the welfare of village people. Village asset management is carried out by planning, utilization, maintenance, administration, reporting as well as guidance and supervision. With this stage of managing village assets, it is hoped that the welfare of village people can increase.